2018
DOI: 10.1073/pnas.1717513115
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenes are the largest source of summertime organic aerosol in the southeastern United States

Abstract: The chemical complexity of atmospheric organic aerosol (OA) has caused substantial uncertainties in understanding its origins and environmental impacts. Here, we provide constraints on OA origins through compositional characterization with molecular-level details. Our results suggest that secondary OA (SOA) from monoterpene oxidation accounts for approximately half of summertime fine OA in Centreville, AL, a forested area in the southeastern United States influenced by anthropogenic pollution. We find that dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

27
242
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 224 publications
(271 citation statements)
references
References 49 publications
27
242
2
Order By: Relevance
“…In the southeastern USA, radioisotope analysis of organic PM determined that 70 % to 80 % of the carbon mass had a modern origin even as correlations were observed between SOM mass concentrations and anthropogenic VOC and CO concentrations (Weber et al, 2007). This finding and those of further field studies in the region together suggested that the organic PM was mainly produced from biogenic VOCs (BVOCs), yet it was modulated by anthropogenic emissions of NO x and SO 2 Xu et al, 2015a, b;Zhang et al, 2018). In the western USA, ground and aircraft measurements observed the highest organic PM increases when air masses containing high BVOC concentrations intercepted anthropogenic emissions (Setyan et al, 2012;Shilling et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the southeastern USA, radioisotope analysis of organic PM determined that 70 % to 80 % of the carbon mass had a modern origin even as correlations were observed between SOM mass concentrations and anthropogenic VOC and CO concentrations (Weber et al, 2007). This finding and those of further field studies in the region together suggested that the organic PM was mainly produced from biogenic VOCs (BVOCs), yet it was modulated by anthropogenic emissions of NO x and SO 2 Xu et al, 2015a, b;Zhang et al, 2018). In the western USA, ground and aircraft measurements observed the highest organic PM increases when air masses containing high BVOC concentrations intercepted anthropogenic emissions (Setyan et al, 2012;Shilling et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Several field observations, mainly in midlatitudes of the Northern Hemisphere, and modeling efforts have suggested that the production of SOM from biogenic precursor compounds becomes more efficient in polluted air (Weber et al, 2007;Hoyle et al, 2011;Huang et al, 2014;Zhang et al, 2018). In the northeastern USA, de Gouw et al (2005) showed that concentrations of organic particulate matter (PM) correlated well with anthropogenic tracers, yet the concentrations of the anthropogenic precursors were insufficient to explain the observed PM concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, applying laboratory-based SOA yields to model the predicted increase in OA, Xu et al (2015) predict only 0.7 µg m −3 of SOA would be produced, substantially lower than the measured nighttime LO-OOA production of 1.7 µg m −3 . The more recent analysis of Zhang et al (2018) found a strong correlation of monoterpene SOA with the fraction of monoterpene oxidation attributed to NO 3 , even for non-nitrate containing aerosol, suggesting an influence of NO 3 even in pathways that ultimately eliminate the nitrate functionality from the SOA, such as hydrolysis or NO 2 regeneration. Ayres et al (2015) used a correlation of overnight organonitrate aerosol buildup with calculated net NO 3 + monoterpene and isoprene reactions to estimate an overall NO 3 + monoterpene SOA mass yield of 40 %-80 %.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, throughout the campaign a major part of SOA is LO-OOA and MO-OOA in southeastern US and hence a large part of SOA formed in the model can be attributed to G/P partitioning. As the majority of the 25 G/P partitioning monoterpene based, monoterpene derived SOA contributes significantly to total SOA formation in southeastern US (Ayres et al, 2015;Zhang et al, 2018). Addition of nitrate reactions can also have a significant contribution to the SOA fraction (Ayres et al, 2015), however, this is not the case in our model, as observed in Figure C6.…”
mentioning
(Expert classified)
“…Monoterpene SOA formation has been shown to be important in the southeastern US (Kim et al, 2015;Zhang et al, 2018) and 20 depends on anthropogenic NOx emissions, which influence daytime oxidation pathways and enhance NO 3 -radical initiated SOA formation during night-time (Xu et al, 2015;Ayres et al, 2015).…”
Section: Introductionmentioning
confidence: 99%